Pastoral leadership for manhood and womanhood - Grudem Wayne; Rainey Dennis (Wheaton, Ill. Crossway Books, 2002)
Sixteen highly regarded men and women tackle practical topics such as how and why to preach on biblical manhood and womanhood, putting the Internet to use, church discipline, small groups, and handling domestic violence. They discuss the personal applic
Keywords: Pastoral counseling -- Congresses. Marriage counseling -- Congresses. Single people -- Pastoral counseling of -- Congresses. View all subjects